2020
DOI: 10.1136/ihj-2019-000032
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Patient Activation Measure (PAM) in clinical settings for patients with chronic conditions: a scoping reviewImplementing the Patient Activation Measure (PAM) in clinical settings for patients with chronic conditions: a scoping review

Abstract: ObjectiveThe Patient Activation Measure (PAM) assesses the knowledge, skills and confidence of patients to manage their health, and has been consistently used as an outcome measure of health interventions. Using the PAM to tailor interventions to a patient’s activation level is less understood. This literature review aimed to examine evidence for interventions using the PAM to tailor care for patients with chronic conditions, including enablers and barriers to implementation, and the impact on quality of care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…There is uncertainty whether interventions aimed at increasing activation improve important health outcomes. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…There is uncertainty whether interventions aimed at increasing activation improve important health outcomes. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that even a 1-point improvement in the latter is clinically relevant and that each point increase in PAM score correlates to a 2% decrease in hospitalization and 2% increase in medication adherence [29]. PAM has been widely adopted, especially in the UK and USA, and it has been used as an outcome measure to evaluate the effectiveness of healthcare interventions [33]. A substantial body of evidence exists to support the use of the PAM in clinical practice for the assessment and targeting of patients that require more support [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review found that the level of PAM was associated with a variety of clinical indicators (e.g. BMI), health outcomes and behaviours [33]. It was also shown that PAM is a significant predictor of healthcare service utilisation and that less activated patients have higher healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐care behaviour varies significantly depending on activation level. Higher PAM scores, regardless of illness type, are associated with improved patient self‐management behaviour (eg, medication adherence, healthy diet, engagement in regular exercise, and stress management) 3,6,7,20 . This is reflected in all types of preventive behaviour, meaning that a person’s activation level is a predictor of self‐care 6 .…”
Section: The Patient Activation Measure Survey Is the Most Common Mea...mentioning
confidence: 99%